Languages, Methodologies and Development Tools for Multi-Agent Systems - Dastani, M. (Springer, 2017)
The 15 revised full papers, presented together with 1 invited paper reporting the aims and achievements of the OpenKnowledge project, were carefully reviewed and selected from 32 submissions. The papers are organized in topical sections on agent reasoning and semantics, declarative languages and technologies, methodologies and design, and development frameworks.